Thyroid dysfunction in patients with childhood-onset medulloblastoma or primitive neuroectodermal tumor - Seung Young Jin; Jung Yoon Choi; Kyung Duk Park; Hyoung Jin Kang; Hee Young Shin; Ji Hoon Phi; Seung-Ki Kim; Kyu-Chang Wang; Il Han Kim; Young Ah Lee; Choong Ho Shin; Sei Won Yang (Korean Society of Pediatric Endocrinology, 2018)
Purpose We investigated the clinical characteristics of patients who developed thyroid dysfunction and evaluated the risk factors for hypothyroidism following radiotherapy and chemotherapy in pediatric patients with medulloblastoma or primitive neuroectodermal tumor (PNET). Methods The medical records of 66 patients (42 males) treated for medulloblastoma (n=56) or PNET (n=10) in childhood between January 2000 and December 2014 at Seoul National University Children's Hospital were retrospectively reviewed. A total of 21 patients (18 high-risk medulloblastoma and 3 PNET) underwent high-dose chemotherapy and autologous stem cell rescue (HDCT/ASCR) Results During the median 7.6 years of follow-up, 49 patients (74%) developed transient (n=12) or permanent (n=37) hypothyroidism at a median 3.8 years of follow-up (2.9-4.6 years). Younger age (<5 years) at radiation exposure (P=0.014 vs. ≥9 years) and HDCT (P=0.042) were significantly predictive for hypothyroidism based on log-rank test. However, sex, type of tumor, and dose of craniospinal irradiation (less vs. more than 23.4 Gy) were not significant predictors. Cox proportional hazard model showed that both younger age (<5 years) at radiation exposure (hazard ratio [HR], 3.1; vs. ≥9 years; P=0.004) and HDCT (HR, 2.4; P=0.010) were significant predictors of hypothyroidism. Conclusions Three-quarters of patients with pediatric medulloblastoma or PNET showed thyroid dysfunction, and over half had permanent thyroid dysfunction. Thus, frequent monitoring of thyroid function is mandatory in all patients treated for medulloblastoma or PNET, especially, in very young patients and/or high-risk patients recommended for HDCT/ASCR.